Depression associated with family functioning and vulnerability among of adolescent students, Tolima - Bedoya, Jaime Gaviria; Suarez, Ramon Paniagua; Posada, Carlos Gonzalez; Ramirez, Sandra Milena Rueda; Gómez, Eilyn Pimienta (Advances in Social Sciences Research Journal, 2018)
Introduction: Depression is considered a common disease worldwide. In Colombia, especially in Villahermosa (Tolima) there are endless social problems that worsen the situation as far as mental health is concerned. The objetive of this study is to explore the potential association of depressive symptoms with family functioning and family vulnerability in adolescents from the municipality of Villahermosa in 2013. Methods: A descriptive cross sectional study was conducted with a survey of 544 students with their consent to participate in the study. A logistic regression was used to determine the association of depressive symptoms with some familiar indicators. Results: The presence of any depressive symptoms was 27,4 % in the total population of adolescents. In addition, the logistic model showed important association with some familiar indicators. Conclusion: Depression in adolescents is a problem with high prevalence, and should be implemented institutional responses to improve mental health and quality of life.